2021
DOI: 10.1002/1348-9585.12219
|View full text |Cite
|
Sign up to set email alerts
|

Health outcomes of psychosocial stress within firefighters: A systematic review of the research landscape

Abstract: Background and Objectives Much of the research surrounding firefighter health has concerned the hazards intuitively associated with the occupation, such as physical, thermal, and chemical risks. However, an additional aspect of their work environment, psychosocial stressors, has begun to attract a growing level of attention. Work‐related psychosocial stress may best be described as mental and emotional strain caused by a combination of workplace events and characteristics, and the objective of our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 79 publications
0
33
0
2
Order By: Relevance
“…1,2 Accordingly, occupational stress can have adverse effects on firefighters' health and well-being. 3 Previous epidemiological studies have shown that occupational stress is associated with an increased risk of noncommunicable chronic diseases 4 such as cardiovascular diseases, 5,6 musculoskeletal disorders, 7,8 mental health, 9,10 and adverse reproductive health outcomes. 11 The effort−reward imbalance (ERI) questionnaire has been widely used to measure psychosocial work environments to identify occupational stress.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,2 Accordingly, occupational stress can have adverse effects on firefighters' health and well-being. 3 Previous epidemiological studies have shown that occupational stress is associated with an increased risk of noncommunicable chronic diseases 4 such as cardiovascular diseases, 5,6 musculoskeletal disorders, 7,8 mental health, 9,10 and adverse reproductive health outcomes. 11 The effort−reward imbalance (ERI) questionnaire has been widely used to measure psychosocial work environments to identify occupational stress.…”
Section: Introductionmentioning
confidence: 99%
“…13 Occupational stress is a significant psychosocial aspect of work environment for firefighters. 3 Occupational health providers need easily applicable, valid, and simple measurements to access psychosocial stress among firefighters. Therefore, this study examined the psychometric properties of the S-ERI questionnaire with a sample of career firefighters in the United States.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Policiais e bombeiros militares são responsáveis por ações de segurança pública e defesa civil em todo o mundo 1 . Existem cerca de 500 mil desses militares distribuídos em mais de 5.000 cidades brasileiras 2 e, ainda que o número crescente de estudos que avaliem as necessidades dos policiais e bombeiros [3][4][5][6][7] , é ínfima a quantidade de instrumentos válidos para esta finalidade. Principalmente no que tange às condições de saúde, demanda física e operacional, assim como as condições de trabalho.…”
Section: Introductionunclassified